Termination of employment in the private sector / Rohana Mohd Noor - Mohd Noor, Rohana (Faculty of Law, 1984)
In any industrial organisation there are two parties: the employer and the employee. The employee earn a living by offering his labour and skill, works for that employer. The terms and conditions of employment are agreed upon when a person commences work. Ordinarily, discord may occur between the employer and the employee over the terms of employment. Hence, innumerable questions may arise out of the employer-employee relationship which may lead to a trade dispute. Trade dispute is defined in the Industrial Relation Act 1967 in Section 2 as any dispute between an employer and his work m e n which is connected with the employment or non-employment or the terms of employment or the conditions of work of any such workmen. The word "non-employment" is evidently one of the issues where by a dispute could be raised. The term "non-employment" does not mean unemployment but a state where an employee ceases to be employed and that means the termination of employment. The essential feature in the termination of employment is the severance of the master-servant relationship, or in modern parlance, the employer employee relationship. "To terminate" means to put an end to; to make to cease or to end and "termination" means to end in time or existence close; cessation or conclusion. The meaning of termination with respect to a contract refers to an ending, usually before the end of the anticipated term of the contract; which termination may be by mutual agreement or may be by exercised of one party or may be by exercise of one party of his remedies due to the default of the other party .Usually termination before the end of the anticipated term of the contract will amount to victimisation by the employer towards the employee and in turn, this will lead the employee to bring an action against the employer for unfairly terminating their services.